A relação entre Hermes, eros e Logos como via de acesso ao conhecimento revelado no Poimandres - CRUZ, Letícia Helena Coca Santa (2022)
The present study seeks to analyze the narrative of the first treatise of the Corpus Hermeticum, entitled Poimandres, aiming at identifying the relevance of the relation between the mythical character of Hermes - which is taken as the ideal hermetic man -, eros - as a power that moves the soul towards the reintegration with an originary and noetic unity - and Logos. We seek to demonstrate how the relationship between these three instances presents itself as the path to access the knowledge that, in this study, is revealed; and that access to the world proposed in this text occurs through the articulation of these elements in our life, in our routine and in the reality of the reader-interpreter. Following Mircea Eliade (2011) and J. Peter Södergård (2003), the perspective that hermetic texts work as self-initiating highlights the relevance of an analysis in the light of philosophical hermeneutics, through which we seek to demonstrate that, much more than a religio mentis, hermeticism comprises a religion of Being: the voluntary opening to a search that is never completely complete, a search for something that is always beyond, in another place, always further ahead, and which presupposes a hermeneutic work by the reader-interpreter-initiate who, questioning their own existential condition, seeks, in this openness to Being and to the sacred, the paths through which they can change their way of understanding the world and being in the world. (AU)